2020
DOI: 10.1016/j.jadohealth.2019.08.031
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Schooling on the Stability and Mutability of Gender Attitudes: Findings From a Longitudinal Study of Adolescent Girls in Zambia

Abstract: Inequitable gender norms are thought to harm lifelong health and well-being. We explore the process of gender attitude change and the role of schooling in shifting or reinforcing gender norms among adolescent girls in Zambia. Methods: We used longitudinal data collected from unmarried, vulnerable girls (aged 10e 19 years) as part of the Adolescent Girls Empowerment Program. We conducted random effects multinomial logistic regression to determine whether schooling-related factors were associated with shifts in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Chae et al [4] report from the Adolescent Girl Empowerment Program in Zambia, where they evaluated the role of age, www.jahonline.org schooling, and region (urban vs. rural) on changing gender norms over time. Attending school in an urban area reinforces equitable gender norms, whereas girls going to school in rural areas did not even experience stable gender norms.…”
Section: Schoolingmentioning
confidence: 99%
See 1 more Smart Citation
“…Chae et al [4] report from the Adolescent Girl Empowerment Program in Zambia, where they evaluated the role of age, www.jahonline.org schooling, and region (urban vs. rural) on changing gender norms over time. Attending school in an urban area reinforces equitable gender norms, whereas girls going to school in rural areas did not even experience stable gender norms.…”
Section: Schoolingmentioning
confidence: 99%
“…Six of the seven articles tackle unique issues in different countriesdBrazil [1,2], South Africa [3], Zambia [4], and the U.S. [5,6]dusing longitudinal data sets. The seventh paper, from Nigeria and Tanzania, uses cross-sectional data and describes associations [7].…”
mentioning
confidence: 99%
“…Recent longitudinal studies from the U.S. show that, in general, male and female gender attitudes became more equitable over the course of adolescence with variation by factors such as country of birth, birth order, age, sex, and parents' gender attitudes [11][12][13]. To our knowledge, only one study has explored this question with longitudinal data from a low income country, finding that at the aggregate level Zambian adolescent girls' gender attitudes became slightly more equitable over time, but that this shift was significant only among urban girls [14].…”
Section: Introductionmentioning
confidence: 98%
“…For example, a study in Bihar, India, shows that exposure to gendertransformative life skills education and sports-coaching programme helped boys accept egalitarian gender role attitudes and notions of masculinity, and reject attitudes about men's controlling behaviours over women/girls and perpetration of violence [25]. Notably, the evaluation found that the program had greater effect sizes among younger boys (13)(14) than older boys (15)(16)(17)(18)(19), although significant improvements were detected among both younger and older boys [26]. A 12-month non-randomized pre-post evaluation of a programme that sought to instill gender-equitable attitudes among adolescent male cricket athletes by sensitizing their coaches in schools in Mumbai, India found that gender attitudes were more equitable among boys whose coaches participated in the intervention as compared to those whose coaches did not [27].…”
Section: Introductionmentioning
confidence: 99%
“…Chae et al. [13] explored in Zambia the role that schooling might play in changing girls' gender norms. A girl's school attendance in urban areas reinforced norms emerging from the comparatively progressive environment, whereas in rural areas, it served as a “liberalizing influence” in more conservative settings.…”
mentioning
confidence: 99%